Synthesizing, Characterization, Studying Antioxidant and Anticancer of Some Metal Complexes with New 7-(3-Hydroxy-phenylazo)-quinoline-8-ol Ligand - Al-rubaye, Noor T.A.; Al–Hamdani, Abbas Ali Salih (Iraqi Journal of Science, 2026)
A new azo dye was synthesized by coupling the diazonium salt derived from 3-aminophenol with 8-hydroxyquinoline.This dye served as a precursor for synthesizing coordination complexes with manganese, chromium, molybdenum and vanadium. The ligand was characterized using¹H and ¹³C NMRspectroscopy, whilethe synthesized materials were characterized by MS, IR and UV-Vis spectrometry, thermogravimetric analysis,and elemental analysis. For the metal complexes, additional measurements such asconductivity, magnetic susceptibility, metal content and chlorine of the complexes were also measured. The results showed that the ligand behaves as trigonal behavior, and that the complexes adopt an octahedral geometry, except for thevanadium square pyramid thatwas given, whichalso showed that the complexes non-electrolytes. The effectiveness of the compounds in inhibiting free radicals was evaluated by the ability to act as an antioxidant which was measured using DPPH as a free radical and Gallic acid as a standard, and the IC50 value was determined. Vanadium and molybdenum complexes were evaluated as anticancer agents for the MCF-7 breast cancer cell line. The vanadium complex gave 97.62 µg/ml, the molybdenum complex gave a higher inhibition value than vanadium.